Taxes or Grants What Revenue Source for Sub-Central Governments? - Blöchliger, Hansjörg (OECD Publishing, 2009)
This paper analyses trends in and driving forces of the revenue composition of sub-central governments (SCG). Between 1995 and 2005 the share of SCG in total government spending increased from 31 to 33%, while the SCG tax share remained stable at around 17%, increasing SCG's dependence on intergovernmental grants. While equal access to public services is the most common justification for such grants, the grant systems of most countries are much larger than required by equalization. Moreover, rather than smoothing out SCG revenue fluctuations over the cycle, grants often tend to exacerbate them. Finally, there is some evidence that grants reduce SCG tax raising effort, inflate SCG spending and increase SCG deficits and debt. The economic crisis will both sharply reduce SCG's own tax revenues and - via budget constraints at the central level - increase pressure on the grant system. The crisis could hence help rethink the SCG revenue mix, their tax structure and the size and design of intergovernmental transfers
Keywords: Economics